Understanding the mediating role of anthropometry and body composition in the relationship between biological maturation and sport-specific performance in young swimmers - de Alencar Matos, M.; Barros, T. A. D. R.; Lima, V. F.; da Costa, M. S. F.; de Oliveira Luz, L. G.; dos Prazeres, T: M. P.; da Silva, N. M. G.; Campos, E. Z.; Nakamura, F. Y.; dos Santos, M. A. M.; dos Santos Henrique, R. (Journal of Sports Sciences, 2025)
This study investigated which anthropometric and body composition characteristics mediate the relationship between biological maturation and swimming performance (Arm propulsive force and 50-m freestyle personal best time) in young athletes. One hundred and thirty adolescent swimmers (53 boys, 13.5 ± 1.7 years; 77 girls, 12.5 ± 1.8 years) were assessed for height, body mass, sitting height, arm span, skinfolds, arm muscle area (AMA) and biological maturation. Arm propulsive force (APF) was determined with the 30-s maximum effort by the tethered swimming test, while swimming performance was also taken as the 50-m personal best time recorded in competition. Mediation analyses were performed using the bootstrapping method and adjusted for chronological age and sex. Arm span, body mass, and lean mass completely mediate the relationship between biological maturation and APF. In addition, stature, arm span and lean mass completely mediate the relationship between biological maturation and 50-m freestyle. Biological maturation establishes a direct relationship with APF only when sitting height and AMA are considered as mediators. Our results show that anthropometric characteristics (stature, body mass and arm span) and lean mass, rather than biological maturation, are related to different measures of swimming performance (APF and 50-m freestyle personal best time) in young athletes.